Glucose determination in human serum by applying inner filter effect quenching mechanism of upconversion nanoparticles - Chen, Xiaojiao; Yang, Zhiying; Chen, Qiong; Zhang, Youyu (Frontiers in Bioengineering and Biotechnology, 2023)
Accurate blood glucose determination is highly essential to the clinical diagnosis and management of diabetes. This work establishes an inner filter effect (IFE) strategy between upconversion nanoparticles (UCNPs) and quinone-imine complex for glucose monitoring in human serum simply and cost-effectively. In this system, the enzyme glucose oxidase (GOx) catalyzes the reaction of glucose into hydrogen peroxide (H2O2) and gluconic acid when compulsion by oxygen. In the presence of horseradish peroxidase (HRP), the produced H2O2 can catalytically oxidize phenol and 4-amino antipyrine (4-AAP) to generate quinone-imine products. The purple-colored quinone-imine complex effectively absorbed the fluorescence of NaYF4:Yb3+, Er3+ UCNPs, leading to the strong fluorescence quenching of UCNPs through IFE. Thus, a new approach was established for glucose monitoring by determining the fluorescence intensity. Under the optimal condition, this approach shows better linearity to glucose from 2-240 μmol/L with a low detection limit at 1.0 μmol/L. Owing to the excellent fluorescence property and background-free interference of the UCNPs, the biosensor was applied for glucose measurements in human serum and got a satisfactory result. Furthermore, this sensitive and selective biosensor revealed great potential for the quantitative analysis of blood glucose or different kinds of H2O2-involved biomolecules for the application of clinical diagnosis.